AD, Volume 6, n° 4, 1981 - Full Issue - issue, Full (Africa Development, 1981)
CONTENTS Les Perspectives de Développement de l'Industrie Sidérurgique en Afrique. Yves JORLIN ........................ 5 What is in a New International Economie Order for the Least Developed Countries of Africa? Fassil G. KIROS ..................... 16 Inga et l'Avenir Industriel du Zafre Alamumbul SHANKAMA ..................... 35 Trade and Development: Classical Theory, Contemporary Reality - With Special Reference to Mozambique Aaron T. GANA .......................... 54 «Administration in Developing Countries»: Riggs Revisited P. HEINECKE ......................... 73 Integrated Rural Development and the Maiginalization of the Peasantry in Nigeria Steven A. NKOM ...................... 82 DOCUMENT Cancun : Doctrines et Résultats A. BENACHENHOU ............................. 94 BOOK REVIEWS / REVUE DES LIVRES D. Wadada Nabudere, Imperialism and Revolution in Uganda Horace CAMPELL ..........................111 Assidon (Elsa), Dekhli (Karina), Jacquemot (Pierre), Raffînot (M. Michel) ļ) Economie et Sociologie du Tiers-Monde .........118 FOCUS ON RESEARCH AND TRAINING INSTITUTES Centre Régional Africain de Technologie (CRAT) ................120 University of Zambia - Institute for African Studies ............ 124